2013
DOI: 10.1118/1.4810938
|View full text |Cite
|
Sign up to set email alerts
|

Dose calculation for electron therapy using an improved LBR method

Abstract: In this research, it is shown that the lateral spread parameter σR(z) increases with cutout size. For radii of circular cutout sizes up to the equilibrium range of the electron beam, the increase of σR(z) with the cutout size is linear. The percentage difference of the calculated PDD curve from the measured PDD data for irregularly shaped cutouts was under 1.0% in the region between the surface and therapeutic range of the electron beam. Similar results were obtained for four electron beam energies (6, 9, 12, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…In our previous publications [12,13], we demonstrated that σ R (z) is dependent on the size of the cutout. By considering this size dependence of σ R (z), we illustrated a significant improvement in the accuracy of PDD and output factor calculations.…”
Section: Introductionmentioning
confidence: 68%
“…In our previous publications [12,13], we demonstrated that σ R (z) is dependent on the size of the cutout. By considering this size dependence of σ R (z), we illustrated a significant improvement in the accuracy of PDD and output factor calculations.…”
Section: Introductionmentioning
confidence: 68%
“…The depth dose data for this research were collected using a Varian 2100C and an ELEKTA Synergy linear accelerator equipped with a 40×40×40 cm 3 water tank and PTW Dosimetry Diode E. The details of the experimental setup for the depth dose measurements are described in our previous publication. 10 The depth dose curves were measured for electron beam energies of 6,9,12, and 16 MeV on Varian 2100C machine and 6, 9, 12, and 15 MeV on ELEKTA Synergy machine. The data were collected using applicator of sizes of 15×15 cm 2 and 14 × 14 cm 2 for Varian 2100C and ELEKTA Synergy machines, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…To account for the deviation from Gaussian shape, an empirical function of cutout size and depth dependent σ R (z) has been introduced posthoc. 10 Recently, Gebreamlak et al 10 have shown that at a given z/R p , the σ R (z) value increases linearly with cutout size until the cutout size reaches to the equilibrium range of the electron beam (R eq ). The slope of the curve is the highest near the surface and decreases as z/R p increases.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations